1997
DOI: 10.1542/peds.99.5.e3
|View full text |Cite
|
Sign up to set email alerts
|

Errors and Correlates in Parental Recall of Child Immunizations: Effects on Vaccination Coverage Estimates

Abstract: ABSTRACT. Objective. We evaluated the accuracy of parental recall of children's immunization histories as compared with provider records and examined how errors in parental recall correlate with sociodemographic characteristics.Design. The validation study was part of a population-based household survey designed to assess immunization levels among Texas children under age 2 years. For 72% (n ‫؍‬ 3278), interviewers used vaccination records from the parent to copy dates for the diphtheria and tetanus toxoids an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
100
0
2

Year Published

2000
2000
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 147 publications
(107 citation statements)
references
References 10 publications
5
100
0
2
Order By: Relevance
“…Research has demonstrated the important effect of different methodologies on the measurement of immunization coverage. [23][24][25][26][27] In particular, the limitations of using parental report have been well documented for immunization assessments, and a similar issue probably exists for lead screening. The use of medical record audits in this study overcomes that limitation and may partially explain the higher screening rates.…”
Section: Discussionmentioning
confidence: 99%
“…Research has demonstrated the important effect of different methodologies on the measurement of immunization coverage. [23][24][25][26][27] In particular, the limitations of using parental report have been well documented for immunization assessments, and a similar issue probably exists for lead screening. The use of medical record audits in this study overcomes that limitation and may partially explain the higher screening rates.…”
Section: Discussionmentioning
confidence: 99%
“…Os resultados apresentados confirmam aqueles obtidos em Salvador -valores elevados de especificidade, quando houve concordância entre informação do responsável e do cartão, sugerindo que a leitura da cicatriz vacinal é um melhor indicador de história de vacinação com BCG do que a informação do cartão ou da família, no Brasil, sugerindo imperfeição na utilização da informação do responsável em relação ao estado vacinal da criança. 15 Observou-se que a informação obtida através do cartão vacinal é incompleta. Neste aspecto, há algumas particularidades a respeito da forma como esses cartões são preenchidos no Brasil.…”
Section: Discussionunclassified
“…32 The lack of concordance between respondent reports and provider reports of some children's hepatitis B immunizations raises concerns about the reliability of parental reports, as has been noted elsewhere. [33][34][35] Respondents may have confused notations on the shot record of Haemophilis influenzae type b vaccine immunizations with those for hepatitis B, because the former is usually recorded as Hib and the latter as HBV. Alternatively, provider records may have not included immunization information from a child's other providers.…”
Section: Discussionmentioning
confidence: 99%